Audiovisual Record of Service-Learning for the Strengthening of Citizenship Competence in Peruvian Universities - Ramos-Santamaía, Mariela Liliana; Jurado-Fernández , Cristian Augusto; Zapatel-Arriaga, Luis Roger Ruben; Moreno-Muro, Juan Pablo (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
Given the growing unwanted social stages such as the abandonment of human beings and the growing social passivity to help them, the objective was established to design and implement a socio-training program of audiovisual workshops transmitted through videoconferences, based on the Solidarity Learning and Service methodology, to strengthen low citizen competence. present in 36% of students at a private Peruvian university. Under a mixed approach, in a sample of 815 students from cycles I, II and III, the program obtained positive results by generating deep introspection, as well as clear commitments in the participants.